2019
DOI: 10.1080/2314808x.2019.1694734
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and efficacy of chitosan membranes in the treatment of skin ulcers

Abstract: Chronic wounds aggravate the patient's indisposition by causing mobility, economic and social problems. Chitosan is a natural polymer that is considered a potent healing agent for skin lesions and has been used previously to manufacture dressings for wounds. The aim of this work was to evaluate the curative effect of chitosan membranes on cutaneous ulcers. The chitosan was characterized by measuring the degree of deacetylation and FTIR. The membranes were obtained by a solvent evaporation technique. Four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Thus, both dressings enhanced wound repair while providing moisture and protection to the wound via properties such as antibacterial 42 and angiogenic properties. 11 12 43 44 45 Another study showed that chitosan gel augmented the synthesis levels of collagen, an endogenous antioxidant, and prevented free radical-mediated tissue injury. 46 47 This endogenous antioxidant may indicate that chitosan prevents the development of necrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both dressings enhanced wound repair while providing moisture and protection to the wound via properties such as antibacterial 42 and angiogenic properties. 11 12 43 44 45 Another study showed that chitosan gel augmented the synthesis levels of collagen, an endogenous antioxidant, and prevented free radical-mediated tissue injury. 46 47 This endogenous antioxidant may indicate that chitosan prevents the development of necrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its biocompatible, biodegradable, non-toxic, antimicrobial, and coagulant properties, chitosan has been applied to skin lesions in the form of gels, sponges, powders, fibers, and films ( Sánchez-Machado et al., 2019 ). Chitosan films are cheap, flexible, and elastic, which is why they can be used for multiple purposes, including wound healing ( López-Cervantes et al., 2019 ). Currently, its healing ability in animals has been described ( Maldonado-Cabrera et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Azad et al [ 90 ] showed the beneficial effect of chitosan membranes at the skin-graft donor site in patients. The effects of chitosan membranes were successfully exploited on skin ulcers in patients [ 91 ]. Nordback et al [ 92 ] proved the beneficial effects of chitosan membranes in cutaneous wounds in rats.…”
Section: Introductionmentioning
confidence: 99%